A New Fork for Clinical Application: Targeting Forkhead Transcription Factors in Cancer - Yang, Jer-Yen; Hung, Mien-Chie (Clinical cancer research, 2009)
Forkhead O transcription factors (FOXO) play a pivotal role in the regulation of a myriad of cellular functions including cell cycle arrest, cell death, and protection from stress stimuli. Activation of cell survival pathways such as phosphoinositide-3-kinase/AKT/IKK or RAS/mitogen-activated protein kinase are known to phosphorylate FOXOs at different sites which cause FOXOs nuclear exclusion and degradation, resulting in the suppression of FOXO's transcriptional activity. Perturbation of FOXO's function leads to deregulated cell proliferation and accumulation of DNA damage, resulting in diseases such as cancer. Emerging evidence shows that active FOXO proteins are crucial for keeping cells in check; and inactivation of FOXO proteins is associated with tumorigenesis, including breast cancer, prostate cancer, glioblastoma, rhabdomyosarcoma, and leukemia. Moreover, clinically used drugs like paclitaxel, imatinib, and doxorubicin have been shown to achieve their therapeutic effects through activation of FOXO3a and FOXO3a targets. In this review, we will focus the novel functions of FOXOs revealed in recent studies and further highlight FOXOs as new therapeutic targets in a broad spectrum of cancers.